Individual differences in the behavioral responsiveness of F1 Holstein-Gyr heifers to the training for milking routine - Paranhos da Costa, Mateus J.R. [UNESP]; Taborda, Paula A.B. [UNESP]; de Lima Carvalhal, Monique V. [UNESP]; Valente, Tiago S. [UNESP] (Elsevier, 2021)
The objective of this study was to assess individual differences in behavioral responses of F1 Holstein-Gyr heifers subjected to habituation protocols to humans and milking procedures. Training was divided in two phases (P1 and P2): habituation to humans (P1), and to the milking parlor and human physical contact (P2). Flight distances (FD) were assessed during P1, and numbers of steps and kicks (as binary) were recorded during P2. The last two measurements and milking reactivity (scored from 1 = cow stands quietly to 8 = cow is very agitated) were recorded during the first four days of milking. Repeated behavioral measurements were used to evaluate individual changes fitting a linear regression for each animal, and the b-coefficients were used to classify heifers as habituated, neutral or sensitized. The percentages of assessment days that each heifer/cow kicked during P2, and during the first four days of milking were calculated. Pearson's correlation coefficients between b-coefficients were estimated. General linear models were fitted to assess the effects of interval classes (defined by the number of days between the last day in training and the first day in miking) and behavioral responses during P1 and P2 on milking reactivity and number of steps on the first day of milking and on b-coefficients of these variables. Individual differences in behavioral responses were observed. Most heifers (∼87 %) habituated during P1 and ∼ 44 % of them reduced number of steps during P2. Almost 52 % of the heifers did not step or exhibit only one step, and ∼93 % of them did not kick when fitting the milking cluster in the first day of milking. Around 56 % of them increased the number of steps along milking assessments, while ∼33 % reduced it. The b-coefficients of FD and for the number of steps in P2 were not associated to the b-coefficients of milking assessed variables. The b-coefficient and the number of steps on the first assessment day of P2 showed a significant effect (P < 0.05) on milking reactivity scores (F = 6.06 and 6.54, respectively) and number of steps (F = 5.73 and 7.88, respectively) assessed in the first day of milking. None of the other independent variables showed significant effect on b-coefficients of milking reactivity scores and number of steps during milking. We conclude that training reduces fear to humans and cows’ reactivity to milking, and that individual differences between heifers play an important role in the training results.
Keywords: Dairy cattle; Habituation; Milking; Reactivity; Temperament